Geriatric neuropsychology : assessment and intervention - Attix, Deborah K.; Welsh-Bohmer, Kathleen A. (Guilford Press, 2006)
This major clinical reference and text is the first volume to systematically address the entire process of neuropsychological assessment and intervention with older adults. The expert editors and contributors detail the current state of knowledge about frequently encountered conditions ranging from mild cognitive impairment to progressive, stable, and reversible dementias. Evidence-based assessment and intervention strategies are described, and specific guidance is provided for linking neuropsychological evaluation to individualized treatment planning. Demonstrating an array of cognitive training, compensatory, and psychotherapeutic approaches, the volume shows how these can successfully be used to improve patients' functioning and quality of life.